Reuse and Mechanochemical Processing of Ore Dressing Tailings Used for Extracting Pb and Zn; Materials; Vol. 16, iss. 21 - Golik V. I. Vladimir Ivanovich; Klyuev R. V. Roman Vladimirovich; Martyushev N. V. Nikita Vladimirovich; Kondratjev V. V. Viktor Viktorovich; Tynchenko V. S. Vadim Sergeevich; Gladkikh V. A. Vitaly Aleksandrovich; Yushkova L. V. Lyudmila Valerjevna; Brigida V. S. Vladimir Sergeevich (2023, 2023)
Title screen